2010
DOI: 10.1186/1476-4598-9-173
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of retinoblastoma gene mutations disturbing apoptosis in human breast cancers

Abstract: BackgroundThe tumor suppressor pRb plays a key role regulating cell cycle arrest, and disturbances in the RB1 gene have been reported in different cancer forms. However, the literature reports contradictory findings with respect to a pro - versus anti - apoptotic role of pRb, and the consequence of alterations in RB1 to chemotherapy sensitivity remains unclear. This study is part of a project investigating alterations in pivotal genes as predictive factors to chemotherapy sensitivity in breast cancer.ResultsAn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 36 publications
(61 reference statements)
3
41
3
Order By: Relevance
“…Peak areas of all MLPA products resulting from ATM specific probes were normalized and compared to references as previously described [24]. …”
Section: Methodsmentioning
confidence: 99%
“…Peak areas of all MLPA products resulting from ATM specific probes were normalized and compared to references as previously described [24]. …”
Section: Methodsmentioning
confidence: 99%
“…Now, with improved therapy and better survival for their RBs it has become clear that these individuals have an increased risk of other cancers later in life as well. 107 Somatic alterations of RB1, including large deletions and promoter methylations, have been detected in different cancer forms, including breast cancer (see references in Berge et al 108 ). In a recent paper, Witkiewicz et al 109 found an RB-deficiency gene expression signature to be associated with increased chance of a pathological complete response among breast cancer patients receiving primary chemotherapy with 5-fluorouracil, adriamycin and cyclophosphamide, but also patients treated with combined anthracycline-and taxane-containing regimens.…”
Section: Tp53 Analogues Tp63 and Tp73mentioning
confidence: 99%
“…In contrast, we found RB1 point mutations and intragenic deletions, albeit rare, to be associated with lack of response to anthracyclines and mitomycin in primary as well as metastatic breast cancers. 108,110 Interestingly, these mutations were located in the protein pocket domain and have never been reported as germline mutations in RB families (Table 2).…”
Section: Tp53 Analogues Tp63 and Tp73mentioning
confidence: 99%
“…This variation is located in the spacer region, previously assumed to be non-essential to peptide-binding activity of the pRb pocket by many authors [27]. Recent study employing Clustal X using default parameters [30], a multiple sequence alignment of the pRb spacer region including sequences from eight different species (cow, mouse, chicken, newt..) showed that the spacer region is fairly well conserved. This finding indicates that the spacer region is important.…”
Section: Discussionmentioning
confidence: 99%